Age-Specific Nesting Performance by Northern Bobwhites - Ryan S. Miller; William E. Palmer; Shane D. Wellendorf (National Quail Symposium Proceedings, 2017)
Greater reproductive productivity of adult versus juvenile northern bobwhites (Colinus virginianus) has been hypothesized as a factor for rapid population growth. Research on bobwhites in the western portions of the species’ range has not supported this hypothesis; however, no effort has been made to investigate age-specific reproduction on population dynamics in the southeast. We measured age- specific reproductive parameters between adult and juvenile bobwhites during 2000–2010. We radio-marked 1,069 females of which 308 were adults and 761 were juveniles. Nests per hens for adults (0.78 nests/hen) was slightly greater than that for juveniles (0.65 nests/hen) (P 1⁄4 0.09). Adult productivity was 1.7 times greater than for juveniles in 4 of 10 years which corresponded to years of population growth. No differences were found in initial clutch sizes or nesting success. Adult hens began incubation earlier than juveniles in all but 1 year suggesting increased nesting may be due to early recrudescence in adults. The magnitude of age-specific reproductive differences in short-lived species like bobwhites is not as great as long-lived species, but has implications for understanding bobwhite population dynamics and harvest.
Keywords: age-specific reproduction; Colinus virginianus; Florida; northern bobwhite; population dynamics; reproductive ecology